Gender and digitalisation supporting women in agribusiness - Okello, Dorothy; Sudarkasa, Michael; Ogunsumi, Lucia (Technical Centre for Agricultural and Rural Cooperation, 2019)
Information and communication technologies (ICTs) can be powerful tools to overcome limited access to information, boosting productivity and facilitating outsourcing, resource sharing and networking. But gender disparities in the use of ICTs across value chain prevent many women from achieving their full potential in the agriculture sector.